Human Sexuality in the History of Redemption - Ramsey, Paul (Journal of religious ethics, 1988)
If Augustine's view of human sexuality is to be understood properly, it must be represented across the history of creation, fall and redemption. His notion of sexuality prior to the fall, although defective in its understanding of personal bodily presence, does integrate sexuality into the essentially human. His account of fallen sexuality expresses not a body-soul dualism but a disordering of the self which finds a partial and redemptive remedy in the "goods of marriage." His treatment of sexuality in relation to redemption-in-course has a distinctively historical dimension that must be respected if sexuality is not to be left merely to the endless rhythms of nature, but drawn into the human story in its Christian telling.